1997
DOI: 10.1021/jm9605344
|View full text |Cite
|
Sign up to set email alerts
|

3α-Hydroxy-3β-(phenylethynyl)-5β-pregnan-20-ones:  Synthesis and Pharmacological Activity of Neuroactive Steroids with High Affinity for GABAA Receptors

Abstract: Neuroactive steroids that allosterically modulate GABAA receptors have potential uses as anticonvulsants, anxiolytics, and sedative-hypnotic agents. Recently, a series of pregnanes substituted with simple alkyl groups at the 3 beta-position were synthesized and found to be active in vitro. The present report describes the synthesis of a series of substituted 3 alpha-hydroxy-3 beta-(phenylethynyl)pregnan-20-ones and their in vitro structure-activity relationship determined by their potency for inhibition of [35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 17 publications
4
30
0
Order By: Relevance
“…GX is developed as a rational analog of AP, which is a potent positive allosteric agonist of GABA-A receptors (Carter et al, 1997). Since neurosteroids exhibit greater selectivity towards extrasynaptic receptors, the results from this study confirm that the antiseizure effect of GX is mostly due to its preferential interaction with GABA-A receptors besides its actions on synaptic receptors (Carver et al, 2014;Carver and Reddy, 2016).…”
Section: Role Ofsupporting
confidence: 54%
See 3 more Smart Citations
“…GX is developed as a rational analog of AP, which is a potent positive allosteric agonist of GABA-A receptors (Carter et al, 1997). Since neurosteroids exhibit greater selectivity towards extrasynaptic receptors, the results from this study confirm that the antiseizure effect of GX is mostly due to its preferential interaction with GABA-A receptors besides its actions on synaptic receptors (Carver et al, 2014;Carver and Reddy, 2016).…”
Section: Role Ofsupporting
confidence: 54%
“…Therefore, GX possesses higher bioavailability and provides a more favorable pharmacokinetic profile as a promising antiepileptic drug. Although GX was previously tested in recombinant 112L GABA-A receptors (Carter et al, 1997), its precise mode of action on native hippocampal neurons remained largely unclear. Here we demonstrated that GX is a potent allosteric modulator of both synaptic and extrasynaptic GABA-A receptors in native hippocampal neurons.…”
Section: Gx Activation Of Extrasynaptic δGaba-a Receptors and Tonic Imentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with the proposed existence of an auxiliary binding pocket in the 5-neurosteroid binding site, that could allocate small lipophilic as well as phenylacetylenic 3-substituents present in several analogues that have shown a high inhibitory activity in TBPS binding assays. 46,47 The introduction of polar groups in the equatorial 12-position of the 5α-neurosteroid series decreased the activity even more than those in 12α-position and than those in position 11. Thus, 12-hydroxy, amino or acetamido derivatives 12, 24, and 19 were less active than their 11-counterparts analogues 44 and 48, while the 12α-hydroxy derivative 15 was more active than the corresponding 12-hydroxy 12 and 11α-hydroxy 39 derivatives.…”
Section: Biological Activity At the Gaba A Receptor And Sar Analysismentioning
confidence: 99%